Integration of nursing professionals, education and healthcare services: a strategic model to empower nurses and shape healthcare policy in India - Baretto, Janifer Shiny; Ananda; Umar, Mohammed; Charakapu, Manjula; Suhashini; Devabaktula, Indhumathi; Dolly (International Journal of Research in Medical Sciences, 2025)
Nurses form the backbone of India’s healthcare system, yet their contributions to health policy, education, and service integration remain underutilized. Effective integration of nursing professionals, education, and healthcare services is essential for advancing universal health coverage (UHC), reducing health disparities, and optimizing the quality of care. This review explores how aligning nursing education with service delivery and policy frameworks can empower nurses to lead reforms and shape healthcare policy in India. A comprehensive search of PubMed, BMJ Open, CINAHL, and PKP-indexed journals was conducted for studies published between 2005 and 2025. Inclusion criteria targeted empirical studies, national health reports, and review articles focused on the nursing profession’s involvement in health policy, service delivery, and education integration. Thematic analysis and narrative synthesis were applied using the IMRAD framework. Out of 2,341 records, 46 studies were included. Five central themes emerged: fragmentation between nursing education and practice; insufficient policy representation of nurses; gaps in clinical leadership development; potential of nursing integration models in public health; and global best practices adaptable for India. A nurse-led strategic model emphasizing vertical integration of academic curricula with national health priorities, community engagement, and digital health innovation showed promise in improving both workforce satisfaction and patient care quality. Reforming nursing education and embedding nurses in policymaking and service delivery is vital to strengthening India’s healthcare system. Strategic integration can empower nurses as key agents in shaping equitable, patient-centered health reforms.